Effect of dimethyl fumarate on lymphocyte subsets in patients with relapsing multiple sclerosis. Issue 2 (April 2020) - Buckle, Guy; Bandari, Daniel; Greenstein, Jeffrey; Gudesblatt, Mark; Khatri, Bhupendra; Kita, Mariko; Repovic, Pavle; Riser, Emily; Weinstock-Guttman, Bianca; Thrower, Ben; Loring, Sherrill; Riester, Katherine; et al.
Background: In patients treated with dimethyl fumarate, absolute lymphocyte count decline typically occurs during the first year and then plateaus; early drops have been associated with the development of severe prolonged lymphopenia. Objective: We investigated the effect of dimethyl fumarate on absolute lymphocyte counts and CD4+/CD8+ T cells in patients with relapsing–remitting multiple sclerosis treated with dimethyl fumarate in routine practice. Methods: Lymphocyte data were collected via medical chart abstraction. Primary endpoint: change from baseline in absolute lymphocyte count and CD4+/CD8+ counts at 6‐month intervals following dimethyl fumarate initiation. Results: Charts of 483 patients were abstracted and 476 patients included in the analysis. Mean baseline absolute lymphocyte count (2.23 × 10 9 /l) decreased by ∼39% (95% confidence interval: –41.1 to –37.2) by month 6 and 44% (95% confidence interval: –46.6 to –42.1) by month 12. CD4+ and CD8+ T-cell subsets strongly correlated with absolute lymphocyte count, with greater decreases from baseline to 6 months vs 6–12 months, and in CD8+ vs CD4+ T cells. Prior natalizumab was not a risk factor for lymphopenia. Conclusion: Dimethyl fumarate-associated decline in absolute lymphocyte count in the first 12 months correlated with decline in CD4+ and CD8+ T cells and was independent of prior natalizumab. Absolute lymphocyte count monitoring continues to be an effective strategy to identify patients at risk of prolonged lymphopenia.